Active antithrombin glycoforms are selectively physiosorbed on plasma extracellular vesicles. Issue 9 (23rd September 2022) - Radeghieri, Annalisa; Alacqua, Silvia; Zendrini, Andrea; Previcini, Vanessa; Todaro, Francesca; Martini, Giuliana; Ricotta, Doris; Bergese, Paolo
Abstract: Antithrombin (AT) is a glycoprotein produced by the liver and a principal antagonist of active clotting proteases. A deficit in AT function leads to AT qualitative deficiency, challenging to diagnose. Here we report that active AT may travel physiosorbed on the surface of plasma extracellular vesicles (EVs), contributing to form the "EV‐protein corona." The corona is enriched in specific AT glycoforms, thus suggesting glycosylation to play a key role in AT partitioning between EVs and plasma. Differences in AT glycoform composition of the corona of EVs separated from plasma of healthy and AT qualitative deficiency‐affected subjects were also noticed. This suggests deconstructing the plasma into its nanostructured components, as EVs, could suggest novel directions to unravel pathophysiological mechanisms.